2011
DOI: 10.1080/01431161.2010.532173
|View full text |Cite
|
Sign up to set email alerts
|

Automated segmentation of vegetation structure units in a Mediterranean landscape

Abstract: In Mediterranean regions, the combination of disturbances, life histories, plant regeneration traits, and microhabitat variability form highly heterogeneous vegetation mosaics which shift in space and time. Consequently, structure-based forest management is emerging as a superior alternative to management of vegetation formations in such areas. Delineation of management units in these areas is often based on manual interpretation of aerial imagery coupled with field surveys. Here, we propose an alternative app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…However, previous studies indicate that the East Mediterranean woody species are not necessarily an easy target for classification by remote sensing. Most local vegetation formations are characterized by densely-growing evergreen species, often with similar spectral properties [58][59][60], small intra-annual differences [61] and morphological similarities [62][63][64][65]. To the best of our knowledge, there are currently no studies that use high spatial resolution imagery with a limited number of bands for the classification of East Mediterranean common species.…”
Section: Classification Of East Mediterranean Vegetation By Remote Sementioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies indicate that the East Mediterranean woody species are not necessarily an easy target for classification by remote sensing. Most local vegetation formations are characterized by densely-growing evergreen species, often with similar spectral properties [58][59][60], small intra-annual differences [61] and morphological similarities [62][63][64][65]. To the best of our knowledge, there are currently no studies that use high spatial resolution imagery with a limited number of bands for the classification of East Mediterranean common species.…”
Section: Classification Of East Mediterranean Vegetation By Remote Sementioning
confidence: 99%
“…We did not choose to focus on ideal target species (e.g., large homogeneous canopies with visually distinct phenophases), rather, we examined the local species assembly as-is, including species with challenging spectral and morphological properties with regard to classification by remote sensing [59,60,62,65]; furthermore, after examining the preliminary classification results, we did not see fit to merge or omit species in order to increase overall accuracy.…”
Section: Overhead Data Acquisition and Species Classificationmentioning
confidence: 99%
“…Recently, object-based image analysis (OBIA; [39][40][41]) has been used to process LiDAR data and particularly LiDAR-derived canopy height models (CHM), to delineate individual trees [42][43][44] and forest stands [31,45,46] and to discriminate between different land cover types [47]. Several studies have integrated LiDAR data with other sources to increase the accuracy of vegetation mapping at various scales [48][49][50] and find the best case-specific solutions. Overall, many studies have demonstrated the outstanding capacity of LiDAR data to monitor various stages of forest succession.…”
Section: Introductionmentioning
confidence: 99%
“…Bar Massada et al () classified a vegetation structure polygon layer based on segmentation of remotely sensed height and cover maps derived from LiDAR imagery. We used this layer to calculate the minimum distance to vegetation structure edges and to model animal orientation within a given patch.…”
Section: Methodsmentioning
confidence: 99%